Robot-assisted cannulated compression screw internal fixation for treatment of femoral neck fracture in children: A case series of ten patients - Feng, Wei; Yao, Ziming; Liu, Haonan; Guo, Dong; Zhu, Danjiang; Song, Baojian; Wang, Qiang; Zhang, Xuejun (Frontiers in Pediatrics, 2023)
Purpose: To investigate the safety and efficacy of robot-assisted cannulated compression screw internal fixation in the treatment of femoral neck fracture in children. Methods: We retrospectively reviewed the data of ten children with femoral neck fractures treated by robot-assisted internal fixation from January 2020 to June 2021. The clinical and radiological characteristics, operation duration, and fluoroscopy frequency of robot-assisted screws placement together with the complications and function were evaluated. At the 12-month follow-up, the hip joint function was evaluated using the Ratliff classification. Results: Ten children, six boys and four girls, aged 4–14 years were included. There were eight type II and three type III femoral neck fractures using the Delbet classification. In the process of robot-assisted internal fixation, the median of fluoroscopy frequency was 22 times and the median of operation duration was 47 min. The median of screw parallelism was 1.33° and 0.66° on the anteroposterior and lateral X-ray films, and the degree of screw distribution was 41.86% and 44.93% on the anteroposterior and lateral X-ray films, respectively. At the 12-month follow-up, there were two cases of femoral head necrosis, and fracture healing was achieved in all patients, of which eight fractures were excellent and three were good by the Ratliff function classification. Discussion: The application of robot-assisted cannulated compression screw internal fixation could help us achieve more safe and accurate screw placement, as well as a good treatment effect for children's femoral neck fractures. Level of Evidence: Level IV. retrospective case series.